Characteristics and Outcomes of Palliative Continuous Intravenous Inotrope Support Among Medicare Beneficiaries With Heart Failure - Sarah Chuzi; Jing Gao; Joshua Thariath; Kamal Faridi; Penelope Pekow; Peter Lindenauer; Erica Spatz; Hunter Groninger; Tara Lagu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Continuous intravenous inotropic support (CIIS) can improve symptoms and functional status for patients with stage D heart failure (HF), but characteristics and outcomes of large cohorts treated with CIIS as a palliative therapy have not been described. Methods and Results We identified Medicare fee‐for‐service (FFS) beneficiaries with diagnostic codes for HF in 2016 to 2017. After excluding beneficiaries who received advanced HF surgical therapies 2014 to 2018 and prior CIIS, we included remaining beneficiaries who initiated CIIS from 2016 to 2017. Primary outcomes were rates of admission, death, palliative care, and hospice utilization within 1 year of CIIS initiation. We identified 1 463 942 Medicare beneficiaries with HF in 2016 to 2017, of whom 3706 (0.3%) beneficiaries initiated palliative CIIS (58.9% male, 82.1% White, 67.1% from urban areas, average age 78 [SD=6.8] years). Average Charlson Comorbidity Index Score was 5.8 (SD=3.1). Only 6.5% of CIIS users had a diagnostic code suggesting receipt of palliative care services. Within 1 year of CIIS initiation, 72.2% of beneficiaries had at least 1 all‐cause admission, 55.7% had ≥2 admissions, and 38% had died. Almost 18% of CIIS users had a claim for hospice services; of CIIS users who died, 43.3% had a hospice claim. Conclusions Among Medicare FFS beneficiaries with HF, palliative CIIS is rare and primarily utilized among older beneficiaries with high global comorbidity. Despite the palliative indication, beneficiaries have high rates of admission and low use of palliative care services. Palliative care and associated services should be better integrated into the care of patients with palliative CIIS.